2015
DOI: 10.1016/j.jseaes.2014.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial paleoenvironment characterization across the Permian–Triassic boundary in South China

Abstract: a b s t r a c tWell-preserved marine fossils in carbonate rocks permit detailed studies of the end-Permian extinction event in the marine realm. However, the rarity of fossils in terrestrial depositional environments makes it more challenging to attain a satisfactory degree of resolution to describe the biotic turnover on land. Here we present new sedimentological, paleontological and geochemical (X-ray fluorescence) analysis from the study of four terrestrial sections (Chahe, Zhejue, Mide and Jiucaichong) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 105 publications
2
97
0
Order By: Relevance
“…Observed fungal spores represent various morphotypes (Fig. 5a–e): amerospores - unicellular, aseptae, sphaerical or sack-shaped spores with a highly variable size; phragmospores - spores with transverse septa, and dictyospores - multicellate spores383940. Superficially, some sphaerical fungal spores can resemble other palynomorphs – i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Observed fungal spores represent various morphotypes (Fig. 5a–e): amerospores - unicellular, aseptae, sphaerical or sack-shaped spores with a highly variable size; phragmospores - spores with transverse septa, and dictyospores - multicellate spores383940. Superficially, some sphaerical fungal spores can resemble other palynomorphs – i.e.…”
Section: Resultsmentioning
confidence: 99%
“…4B of Zhang et al, 2016), but as for mud clast nodules of the upper part of the Kayitou Formation, these are in fact loose samples that are not located on the general outcrop picture. Moreover, the previously published sedimentological sections (Peng et al, 2005(Peng et al, , 2006Bercovici et al, 2015) did not describe such pedogenic features within the Kayitou and Dongchan formations. In any case, provided that in the Chahe section, the top of the Kayitou and the base of the Dongchuan formations display some pedogenic features, these, as described by Zhang et al (2016), can only be found in what appears to be a folded and faulted transition area (Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 90%
“…Liu et al, 2012;Deng et al, 2015;Faure et al, 2016). A large number of published studies consider that field areas in Southwest China, and especially the Chahe and Zhejue sections, represent key reference sections to study the terrestrial PTB, the end-Permian mass extinction on land, the gradual transition from terrestrial to marine facies from Permian to Triassic, and to provide correlations with the Meishan marine reference section across the Yangtze Platform (Peng et al, 2005(Peng et al, , 2006Yu et al, 2007Yu et al, , 2008Peng and Shi, 2008;Shen et al, 2011;Bercovici et al, 2015Bercovici et al, , 2016Zhang et al, 2016;Cui et al, 2017). All these studies are based on sedimentological sections considered as stratigraphically continuous across the PT boundary and laterally continuous from the terrestrial environments to the west to the marine deposits in the east.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…These Olenekian wetland communities are possibly a response of an allogenic succession of early pioneers represented by bryophytes and lycophytes that produced spores such as Limatulasporites limatulus and Densoisporites spp. This spore-producing vegetation was thriving globally following the end-Permian mass extinction, forming a marker for the recovery successions in continental environments (Looy et al 1999;Grauvogel-Stamm and Ash 2005;Vajda and McLoughlin 2007;Bercovici et al 2015).…”
Section: Tt1mentioning
confidence: 99%